STRATEGI GURU PENDIDIKAN AGAMA KATOLIK DALAM MENINGKATKAN SELF-EFFICACY SISWA KELAS XI DI SMA - livia depari; Mimpin Sembiring (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Self-efficacy encapsulates a core psychological construct reflecting an individual’s internal conviction in navigating academic assignments, overcoming barriers, and actualizing designated educational objectives. This scholarly inquiry is designed to elucidate the profile of self-efficacy among grade XI pupils at SMA Swasta RK Serdang Murni Lubuk Pakam and to dissect the pedagogical maneuvers deployed by Catholic Religious Education instructors to fortify this trait through theological nurturing, moral maturation, and spiritual guidance. Operationally, this study utilized a qualitative-descriptive methodology. The research informants comprised the institutional head, an educator of Catholic theology, and 12 eleventh-grade students recruited via a purposive sampling mechanism to align with the empirical focus of the study. Data procurement was structured around targeted interviews, direct field observations, and archival tracking, whereas the analytical trajectory proceeded via data reduction, structural display, and contextual inference. The diagnostic insights reveal that the students' self-efficacy resides within a reasonably competent echelon. This is structurally manifested through academic task ownership, cognitive resilience during pedagogical hurdles, and assertiveness in classroom dynamics, notwithstanding a minor segment of pupils still demonstrating unstable confidence and fragmented learning strategies. This performance standard is intrinsically linked to the proactive intervention of Catholic Religious Education teachers, who stimulate student self-efficacy through moral-theological mentoring, interactive spiritual methodologies, Christian role-modeling, institutionalizing religious activities, constructing faith-centric learning circles, and executing reflective performance evaluations. ABSTRAK Self-efficacy merepresentasikan derajat keyakinan personal seorang individu mengenai kapasitas dirinya dalam merampungkan penugasan, merespons rintangan, sekaligus menggapai target yang dicanangkan sepanjang dinamika instruksional. Investigasi ini diproyeksikan untuk memotret potret self-efficacy siswa kelas XI di SMA Swasta RK Serdang Murni Lubuk Pakam sekaligus mengidentifikasi taktik yang diterapkan oleh guru Pendidikan Agama Katolik dalam mengeskalasi aspek tersebut melalui skema internalisasi iman, pematangan moral, serta pendampingan kerohanian. Desain riset ini mengadopsi pendekatan kualitatif dengan metode deskriptif. Klaster informan kunci melibatkan kepala sekolah, pendidik rumpun materi Agama Katolik, serta 12 siswa kelas XI yang dijaring menggunakan teknik purposive sampling demi menjamin kesesuaian basis data riset. Instrumen pengumpulan data dihimpun lewat kombinasi wawancara mendalam, pengamatan lapangan, dan penelaahan dokumen, yang dilanjutkan dengan operasi analisis model interaktif meliputi reduksi, penyajian data, serta penarikan konklusi. Temuan ilmiah membuktikan bahwa efikasi diri siswa berada pada taraf yang cukup memadai. Indikasi ini dicirikan oleh tumbuhnya rasa optimisme dalam menuntaskan kewajiban akademik, ketahanan mental kala menjumpai problem belajar, serta mentalitas yang berani dalam ekosistem kelas, kendati sebagian kecil murid masih memperlihatkan krisis kepercayaan diri serta inkonsistensi taktik belajar. Kondisi makro tersebut didukung penuh oleh kontribusi strategis guru Pendidikan Agama Katolik yang mengupayakan penguatan efikasi diri murid lewat bimbingan teologis-moral, formulas instruksi rohani yang interaktif, keteladanan perilaku Kristiani, stimulasi perayaan liturgis-keagamaan, pengondisian ekosistem belajar berbasis iman, hingga penerapan evaluasi kelas yang bersifat reflektif.